In-hospital surgical treatment for haemorrhage after aesthetic mandibular osteotomy performed as an office-based day surgery: A case report. (December 2017) - Kanke, Kosuke; Abe, Takahiro; Abe, Masanobu; Mori, Yoshiyuki; Hoshi, Kazuto; Takato, Tsuyoshi
Abstract: In East Asia, a square face is considered unattractive, and mandibular contouring surgery is commonly used to give a smooth contour to the lower jaw. Mandibular contouring surgery occasionally involves not only osteotomy of the mandibular angle but also resection of the masseter muscle via an intraoral approach. This type of mandibular contouring surgery poses a risk of injury to the premasseteric branch of the facial artery and massive haemorrhage. Here we report a patient who presented to our hospital with severe haemorrhage, swelling and airway constriction after bilateral mandibular angle and plane osteotomy with resection of the masseter muscle performed elsewhere as an office-based day surgery. The swelling and haemorrhage were treated successfully with emergency bilateral ligation of the facial artery and vein under general anaesthesia. We concluded that the haemorrhage was caused by rupture of the premasseteric branch of the facial artery during the resection of the masseter muscle in a day surgery. Highlights: Our patient had severe complications after mandibular angle and plane osteotomy. Severe swelling and haemorrhage were caused by facial artery rupture. Treatment included bilateral ligation of the facial artery and vein. Haemorrhage of the facial artery can occur after mandibular contouring surgery.